If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3 + -1(x + -5) = 3x + -1(5x + 6) Reorder the terms: 4x + 3 + -1(-5 + x) = 3x + -1(5x + 6) 4x + 3 + (-5 * -1 + x * -1) = 3x + -1(5x + 6) 4x + 3 + (5 + -1x) = 3x + -1(5x + 6) Reorder the terms: 3 + 5 + 4x + -1x = 3x + -1(5x + 6) Combine like terms: 3 + 5 = 8 8 + 4x + -1x = 3x + -1(5x + 6) Combine like terms: 4x + -1x = 3x 8 + 3x = 3x + -1(5x + 6) Reorder the terms: 8 + 3x = 3x + -1(6 + 5x) 8 + 3x = 3x + (6 * -1 + 5x * -1) 8 + 3x = 3x + (-6 + -5x) Reorder the terms: 8 + 3x = -6 + 3x + -5x Combine like terms: 3x + -5x = -2x 8 + 3x = -6 + -2x Solving 8 + 3x = -6 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 8 + 3x + 2x = -6 + -2x + 2x Combine like terms: 3x + 2x = 5x 8 + 5x = -6 + -2x + 2x Combine like terms: -2x + 2x = 0 8 + 5x = -6 + 0 8 + 5x = -6 Add '-8' to each side of the equation. 8 + -8 + 5x = -6 + -8 Combine like terms: 8 + -8 = 0 0 + 5x = -6 + -8 5x = -6 + -8 Combine like terms: -6 + -8 = -14 5x = -14 Divide each side by '5'. x = -2.8 Simplifying x = -2.8
| -3x-12x=175 | | X=717.2+-1x | | X+(x+3.4)=720.6 | | 4x-8=4(x-7) | | y=log(3x^2+5x-2) | | 40x+5(1.5x)=900 | | 4(2x-3)+5(X-1)=23 | | 30-20+20x=10 | | X+(x+7.8)=726.2 | | n-38=50 | | 8+2*(-8)-6= | | -17+5=-4(x+1) | | x+22=3x+6 | | x^2/ | | 8(2c+4)=0 | | 84=4v-2(X-3)-3x | | 160+170+400+x=1000 | | 128=2n+8(n+6v) | | 5/9d=9/4 | | 11x+3=10x+3 | | (3/7)x-1=(2/3)(6x-2) | | (3/7)x-1=(⅔)(6x-2) | | 83=2(-6b+1)-3 | | (3/7)x-1=(2/ | | 11k=13t−7k/2t | | 1+Log[5](-4x)=3 | | 544=-5n-8(7n-7) | | (3z-5)(7-z)=0 | | 2/3y-6=10 | | 3x-4(-2x-5)=2x-3 | | 5x^2+6-51=0 | | h-4+1=3 |